Fork Cleavage-Religation Cycle and Active Transcription Mediate Replication Restart after Fork Stalling at Co-transcriptional R-Loops - Chappidi, Nagaraja; Nascakova, Zuzana; Boleslavska, Barbora; Zellweger, Ralph; Isik, Esin; Andrs, Martin; Menon, Shruti; Dobrovolna, Jana; Balbo Pogliano, Chiara; Matos, Joao; Porro, Antonio; Lopes, Massimo; et al. (Molecular cell, 2020)
Formation of co-transcriptional R-loops underlies replication fork stalling upon head-on transcription-replication encounters. Here, we demonstrate that RAD51-dependent replication fork reversal induced by R-loops is followed by the restart of semiconservative DNA replication mediated by RECQ1 and RECQ5 helicases, MUS81/EME1 endonuclease, RAD52 strand-annealing factor, the DNA ligase IV (LIG4)/XRCC4 complex, and the non-catalytic subunit of DNA polymerase δ, POLD3. RECQ5 disrupts RAD51 filaments assembled on stalled forks after RECQ1-mediated reverse branch migration, preventing a new round of fork reversal and facilitating fork cleavage by MUS81/EME1. MUS81-dependent DNA breaks accumulate in cells lacking RAD52 or LIG4 upon induction of R-loop formation, suggesting that RAD52 acts in concert with LIG4/XRCC4 to catalyze fork religation, thereby mediating replication restart. The resumption of DNA synthesis after R-loop-associated fork stalling also requires active transcription, the restoration of which depends on MUS81, RAD52, LIG4, and the transcription elongation factor ELL. These findings provide mechanistic insights into transcription-replication conflict resolution.